2019
DOI: 10.26418/jebik.v8i2.27540
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepercayaan, Efikasi diri, dan Komitmen Organisasional terhadap Berbagi Pengetahuan Karyawan di Kantor Cabang Utama PT Bank Panin Tbk Kota Pontianak

Abstract: This research aims at examining and analyzing the influence of trust, self-efficacy, and organizational commitment on employees' knowledge sharing at The Main Office of PT Bank Panin Tbk Kota Pontianak. Research method applied is causal approach survey in form of quantitative causal decription. Census technic is used to collect the primary data. A Total of 70 questionnaires were distributed among the employees. Collectively, 51 usable questionnaires were returned. Secondary data was elicited from interviewing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…This supports (H4), which asserts that commitment to knowledge sharing has a favorable impact. The findings of this study support earlier studies by [7] and [8], both of which found a positive and substantial relationship between commitment and knowledge sharing.…”
Section: The Effect Of Commitment To Information Sharingsupporting
confidence: 91%
See 1 more Smart Citation
“…This supports (H4), which asserts that commitment to knowledge sharing has a favorable impact. The findings of this study support earlier studies by [7] and [8], both of which found a positive and substantial relationship between commitment and knowledge sharing.…”
Section: The Effect Of Commitment To Information Sharingsupporting
confidence: 91%
“…Katopas Jaya Abadi in its entirety and found that dedication has a favorable and significant impact on knowledge sharing. [8] states that commitment has an effect on sharing information in the form of knowledge. With this, a stronger commitment can encourage better information sharing.…”
Section: Introductionmentioning
confidence: 99%
“…Efikasi diri berkaitan erat dengan komitmen organisasi dimana bila pegawai mempunyai efikasi diri yang tinggi maka komitmen terhadap apa yang dikerjakannya juga akan semakin tinggi, (Sumual, 2014). Individuindividu dengan efikasi diri tinggi memiliki komitmen dalam memecahkan masalahnya dan tidak akan menyerah ketika menemukan bahwa strategi yang sedang digunakan itu tidak berhasil, (Verianto, 2019). Hasil penelitian Sinaga (2018) membuktikan bahwa penguatan Efikasi diri berpengaruh secara signifikan terhadap peningkatan komitmen organisasi.…”
Section: Latar Belakangunclassified
“…Employee trust in the organization will help the company achieve its goals because employee trust goes hand in hand with increasing productivity and employee engagement with the organization (Setiawan et al, 2020). Employee trust is a form of self-confidence in an organization that encourages employees to voluntarily share knowledge with colleagues and the organization (Verianto, 2019) . Trust is an important characteristic of employee ethical behavior in institutions that plays a role in work productivity and performance results (Vlachos & Anagnostopoulos, 2023).…”
Section: Introductionmentioning
confidence: 99%